Penyuluhan Penggunaan Obat Cacing untuk Anak Usia Dini di Sekolah Dasar Negeri 6 Wawo - Musdar, Tamzil Azizi; Bahri, Kasmitha; Iwan, Iwan; Sari, Melanta; Yunita, Amelia; Putriani, Dian Rohma; Yudasti, Alham Ahmad; Ramadani M.J, Cahaya; Nanda, Dhina Aprilia; Akmal, Akmal; Ariawan, I Putu; Samsidar, Samsidar; Basiruddin, Basiruddin; Ilmah, Ilmah; Indayani, Riska (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service activity titled “Deworming Education for Early Childhood Students at SDN 6 Wawo, Walasiho Village, Wawo District, North Kolaka Regency” aims to increase students’ knowledge about the importance of maintaining body health from worm infections. The activity was carried out through interactive counseling and direct demonstrations on prevention methods and the importance of taking deworming medicine regularly. This activity was motivated by the low awareness among children regarding the dangers of worm infections that can affect growth and learning concentration. The results showed an increase in students’ understanding of personal hygiene and the benefits of deworming medicine. This program is expected to foster healthy living habits from an early age and prevent worm-related diseases.